Tinseltown gangsters: the rise and decline of the mob in Hollywood - Sussman, Jeffrey (Rowman & Littlefield, 2024)
"Like sharks to blood in the water, the mob arrived in Hollywood greedy and ready to tear away huge chunks of cash. Opportunistic mobsters saw labor unions as the means for muscling into the movie industry and extorting millions of dollars from studio bosses"-- Provided by publisher